2017
DOI: 10.1111/ggr.12158
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Precise Silicon Isotope Analysis of Sulfur‐ and Iron‐Rich Samples by MCICPMS

Abstract: Silicon isotope determination of sulfur‐rich samples by MC‐ICP‐MS can be challenging because cation‐exchange chromatography used for Si purification does not efficiently remove anionic sulfur species. Results for pure Si standard solutions with addition of sulfate showed shifts of up to +1.04 ± 0.10‰ (2s) in δ30Si. Doping of both standard solutions and samples with S to a fixed S/Si ratio can eliminate the relative change in instrumental mass fractionation due to variable S/Si in samples and also boosts the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
10
2
Order By: Relevance
“…Although the statistical approach revealed a shi in d 30 Si of −0.06& produced by sulfate and a mixture of sulfate and chloride contamination, this shi is substantially smaller than those reported by previous authors with values of +1.4&, 8 +0.28& 10 and +1.04&. 9 Moreover, considering the analytical uncertainties associated with Si isotope measurements by MC-ICP-MS, the shi in d 30 Si of −0.06& for both groups (sulfate only and sulfate + chloride) fall within errors of the undoped NBS-28, whose d 30 Si = −0.01 ± 0.09& (2SD), as well as within the long-term reproducibility of ±0.11& (2SD) obtained for the BHVO-2 standard. Consequently, we concluded that despite observing a matrix effect (−0.06&) produced by sulfate, chloride, or a mix of both anions, this effect is not distinguishable given our current measurement uncertainties.…”
Section: Sulfate and Chloride Matrix Effectcontrasting
confidence: 65%
See 2 more Smart Citations
“…Although the statistical approach revealed a shi in d 30 Si of −0.06& produced by sulfate and a mixture of sulfate and chloride contamination, this shi is substantially smaller than those reported by previous authors with values of +1.4&, 8 +0.28& 10 and +1.04&. 9 Moreover, considering the analytical uncertainties associated with Si isotope measurements by MC-ICP-MS, the shi in d 30 Si of −0.06& for both groups (sulfate only and sulfate + chloride) fall within errors of the undoped NBS-28, whose d 30 Si = −0.01 ± 0.09& (2SD), as well as within the long-term reproducibility of ±0.11& (2SD) obtained for the BHVO-2 standard. Consequently, we concluded that despite observing a matrix effect (−0.06&) produced by sulfate, chloride, or a mix of both anions, this effect is not distinguishable given our current measurement uncertainties.…”
Section: Sulfate and Chloride Matrix Effectcontrasting
confidence: 65%
“…Our results clearly indicate that no signicant matrix effect is induced by the presence of chloride for [Cl − ]/[Si] ratio < 5.65. In contrast to the ndings of Van Den Boorn et al, 8 Chen et al 9 and Hughes et al, 10 ]/[Si] = 0.12 and 0.15 that show a slightly larger deviation of −0.12& and −0.11&, respectively. However, all those values remain within uncertainties of the undoped NBS-28.…”
Section: Sulfate and Chloride Matrix Effectmentioning
confidence: 62%
See 1 more Smart Citation
“…The term “concentration mismatch” was used throughout this study to be consistent with previous studies, 70,72,107 but we emphasize that ion intensity mismatch is the fundamental source for biased isotope measurements. Although, typically, ion intensity is directly related to the analyte concentration, it can also be affected by other factors, such as the presence of certain matrix elements, 109,110 and instrument drift (see our results below), which could also result in biased measurements. In this contribution, we use “concentration mismatch” in a broader sense to include “ion intensity mismatch” caused by any reason.…”
Section: Resultsmentioning
confidence: 79%
“…One additional problem of Si isotope analyses in metallic fractions of EC is the high abundance of sulfides and phosphides associated with Si‐bearing kamacite (Weisberg & Kimura, 2012). The cation exchange ion chromatography procedure does not effectively remove S and P from Si, and therefore, an overabundance of these anions in the samples might have an influence on the measured Si isotope composition (Chen et al., 2017; van den Boorn et al., 2009). The matrix effect of anions on mass spectrometric analyses of Si was tested at GFZ by doping purified NBS‐28 solution with phosphate, sulfate, and nitrate anions to produce different [anion]/[Si] mass ratios (μg μg −1 ) from 0.01 to 6.4 (Oelze et al., 2016).…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%